The Responsibility of Higher Education Institutions in Human Trafficking Cases Disguised as Internships: An Analysis of Islamic Criminal Law - Hanif, M. Afwan; Mukhsin, Abd. (State of Islamic Institute Langsa, 2025)
Ideally, higher education institutions should act as entities that protect students' rights and provide quality education without abusing their position for harmful purposes. However, in reality, some universities are involved in practices that can harm students, including the misuse of internship programs that lead to human trafficking crimes. This study aims to analyze the legal responsibilities of higher education institutions in cases of human trafficking that occur within internship programs, using an Islamic criminal law approach. This article is categorized as a qualitative-based literature study. The methodology used is a normative juridical approach. The research results show that human trafficking cases in Jambi demonstrate complexity, involving both individuals and corporations, with different legal sanctions under Law No. 21 of 2007 and Islamic criminal law. Higher education institutions, such as Universitas Jambi, play an important role in providing assistance to victims, supporting legal processes, and collaborating with relevant parties to combat human trafficking, reflecting their moral and social responsibility.